1995
DOI: 10.1111/j.1432-1033.1995.tb20468.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of Zinc Protopheophorbide b with NADPH-Protochlorophyllide Oxidoreductase from Etiolated Wheat (Triticum aestivum L.)

Abstract: A preparation of prolamellar bodies from wheat etioplasts was used as a source for NADPH-protochlorophyllide oxidoreductase (pchlide reductase). The enzyme was solubilized with Triton X-100 after reduction of the endogenous photoconvertible protochlorophyllide a to chlorophyllide a by saturating illumination. Protochlorophylls a and b, protochlorophyllide a and zinc protopheophorbide b were added to the soluble enzyme preparation to determine if they were reduced in the dark or in the light. None of the compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…The Pchlide specificity of POR is largely unknown. However, detergenttreated POR enzyme preparations from wheat etioplasts convert 3-monovinyl Pchlide a but not the esterified forms of this compound to Chlide (Schoch et al, 1995), which confirms previous results reported by Griffiths (1980). The wheat enzyme also converts Zn2'-protopheophorbide b, which is the Zn2+ analog of Pchlide b, to Zn'+-pheophorbide (Schoch et al, 1995).…”
Section: This Review)supporting
confidence: 79%
See 4 more Smart Citations
“…The Pchlide specificity of POR is largely unknown. However, detergenttreated POR enzyme preparations from wheat etioplasts convert 3-monovinyl Pchlide a but not the esterified forms of this compound to Chlide (Schoch et al, 1995), which confirms previous results reported by Griffiths (1980). The wheat enzyme also converts Zn2'-protopheophorbide b, which is the Zn2+ analog of Pchlide b, to Zn'+-pheophorbide (Schoch et al, 1995).…”
Section: This Review)supporting
confidence: 79%
“…However, as described above for Pchl a, the esterified forms of Pchlide b (i.e. Pchl b) could not be photoreduced by this enzyme preparation (Schoch et al, 1995).…”
Section: This Review)mentioning
confidence: 99%
See 3 more Smart Citations